Tradisi Pembuidau Dan Kandeko Di Kampung Mambui Distrik Urifaisey, Kabupaten Waropen, Papua Dalam Pelaksanaan Etnokonservasi Tumbuhan Mangrove - Sujarta, Puguh (Fakultas Biologi Universitas Gadjah Mada, 2024)
Abstract: Papua has natural resources, biodiversity and local wisdom (to manage coastal and marine resources). Research aims: first, to determine knowledge of the Pembuidau and Kandeko traditions; second, to find out knowledge about ethnoconservation of mangrove plants. Data collection techniques using survey, interview and documentation methods. The survey results show that there are seven species of mangrove plants that are utilized by the community, including the leaves, stems, roots, flowers and fruit. Conclusion: first, the Pembuidau and Kandeko Traditions are local wisdom of the Mambui community, including the management of mangrove ecosystems in the form of cleaning the place and planting mangrove plants; second, Ethnoconservation of mangrove plants in a range of uses by the community. The recommendation is to preserve this tradition to maintain the mangrove ecosystem.